Facing forward after Ebola: questions for the next director general of the World Health Organization. (18th May 2016) - Sridhar, Devi; Kickbusch, Ilona; Moon, Suerie; Dzau, Victor; Heymann, David; Jha, Ashish K; Saavendra, Jorge; Stocking, Barbara; Woskie, Liana; Piot, Peter
Abstract : In light of heavy criticism of the WHO's handling of the Ebola outbreak, the election process for the next director general will be under intense scrutiny. Devi Sridhar and colleagues outline the key questions on epidemic preparedness for prospective candidates